Managerial ownership changes and mutual fund performance - Thorsten Martin; Florian Sonnenburg (University of Cologne, Centre for Financial Research (CFR), 2015)
We study the dynamics of fund manager ownership for a sample of U.S. equity mutual funds from 2005 to 2011. We find that ownership changes positively predict changes in future risk-adjusted fund performance. A one-standarddeviation increase in ownership predicts a 1.6 percent increase in alpha in the following year. Fund managers who are required to increase their ownership by fund family policy show the strongest increase in alpha. They do so by increasing their trading activity in line with the view that higher ownership aligns interests of managers with those of shareholders and induces higher effort.
Keywords: G11; G14; G20; G23; 330; Mutual Funds; Fund Manager Ownership Changes; Fund Performance Predictability; Incentive Alignment; Superior Information